Efecto de los nanoencapsulados de tres aceites esenciales en la producción y calidad de huevo de gallinas de postura comercial - Armas Azabache, Ana Vanessa (2023)
The objective of this research was to evaluate the effect of nanoencapsulated essential oils of soursop, lemon and eucalyptus on the production and quality of eggs of commercial laying hens. For this, 160 birds were used from 16 to 31 weeks of age, distributed in 5 treatments: T0: Control, T1: 33.4% Soursop, 33.3% Lemon, 33.3% Eucalyptus, T2: 50% Soursop, 25% Lemon, 25 % Eucalyptus, T3: 25% Soursop, 50% Lemon, 25% Eucalyptus and T4: 25% Soursop, 25% Lemon, 50% Eucalyptus. The percentage of posture T0, T1, T2, T3 and T4 were 71.02%, 72.17%, 66.56%, 69.16%, 75.04%; (P<0.05), observing significant statistical differences and weekly food consumption, for the treatments 1.80 kg, 1.86 kg, 1.80 kg, 1.84 kg, 1.85 kg; and 101.48kg,101.54kg, 101.49kg, 101.34kg, 101.46kg; respectively; not observing significant statistical differences between treatments (P>0.05). For the parameters resistance, Haugh Index, bud height, T1 obtained the best numerical value. Regarding egg weight, egg color and shell thickness, significant statistical differences were found (P<0.05), with treatments T1 and T3 being superior compared to T0. Likewise, for yolk color, yolk diameter, yolk index, there were no statistical differences, but the treatments T0, T3 and T4 were numerically superior. It is concluded that the nanoencapsulated essential oils added to the diet of commercial laying hens improve their productive parameters, and significantly increase egg weight and shell thickness as a characteristic of egg quality (P<0.05).